Values-based modes of production and consumption: analyzing how food alternatives transform the current food regime - Plank, Christina; Stotten, Rike; Hafner, Robert (Frontiers in Sustainable Food Systems, 2024)
The current food regime has experienced a multidimensional crisis, driving further unjust and unsustainable development. Various food alternatives address these challenges by promoting different modes of alternative production and consumption. However, they are not extensively theoretically addressed within the food regime literature. Thus, we suggest analyzing food regimes with further social science theories to explore food alternatives and their possible contributions to transforming the present food regime. Drawing on a combination of critical state theory, the social capital concept, and territorial approaches, we introduce an interdisciplinary conceptual framework called values-based modes of production and consumption. We assume that food alternatives are based on values other than economic ones, such as democracy, solidarity, or trust. The framework allows examining perspectives of transformation that focus on conflict or cooperation and how they can be interlinked. We aim to determine entry points for analyzing food alternatives within the current food regime because these enable an exchange between debates that are usually taking place alongside each other. By linking them, we aim to inspire further insightful interdisciplinary research.